THE IMPACT OF OXIDATIVE STRESS ON RENAL FUNCTION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Oxidative stress is a key pathogenic mechanism contributing to acute and chronic kidney injury. Excessive production of reactive oxygen species (ROS) overwhelms renal antioxidant defenses, resulting in cellular damage, inflammation, vascular dysfunction, and fibrosis. This article reviews molecular mechanisms of oxidative stress–induced renal injury, summarizes recent experimental and clinical findings, and discusses therapeutic strategies aimed at attenuating oxidative damage to improve renal outcomes.